The feasibility and effectiveness of virtual reality meditation on reducing chronic pain for older adults with knee osteoarthritis. Issue 7 (4th July 2022) - Sarkar, Tara D.; Edwards, Robert R.; Baker, Nancy
Abstract: There is an urgent need for safe and effective nonpharmacologic approaches to treat chronic knee pain in older adults. Although virtual reality (VR) has shown some effectiveness for acute pain, there is limited evidence on the effects of VR on chronic pain particularly with older adult populations. This single application, within‐subject pilot study evaluated the feasibility and effectiveness of VR as a clinical treatment for older adults with chronic osteoarthritis knee pain. Nineteen participants aged 60+ years old participated in a 10‐min VR meditation program. Data on pain and affect were collected immediately prior to, post, and 24–48 h after the VR. Results suggest that VR meditation had significant moderate to large analgesic effects on knee pain intensity, primarily during VR ( d  = 1.10) and post VR ( d  = 0.99), with some lasting effects into next day ( d  = 0.58). The findings also suggest VR meditation intervention had a positive effect on affect, with a significant large decrease in negative affect scores pre‐ to post‐VR ( d  = 1.14). The significant moderate to large decreases in pain interference for normal work ( d  = 0.71), mood ( d  = 0.53), sleep ( d  = 0.67), and enjoyment of life ( d  = 0.72) suggest that older adults may have a higher ability to participate in meaningful daily activities up to 24–48 h after VR meditation. VR appears to be a feasible and effective nonpharmacological tool for older adults to treat chronic overall and knee‐specific pain.